The first complete mitochondrial genome of the Northern Pacific deep-sea goniasterid sea star Ceramaster japonicus (Sladen, 1889) determined using NGS-based shotgun sequencing - Masaki Yamamoto; Shimpei F. Hiruta; Mikihito Arai; Moe Shimizu; Christopher L. Mah; Toshihiko Fujita; Davin H. E. Setiamarga (Mitochondrial DNA. Part B. Resources, 2021)
The full mitogenome of an ethanol-preserved museum specimen of Ceramaster japonicus was determined using the NGS Illumina MiSeq platform. The specimen was collected from Tosa Bay, Japan, facing the Pacific Ocean (33.0781 N 134.0601 E), at 700 m depth in 2011. The mitogenome shows a typical metazoan genomic structure, with all of the 37 genes included in its 16,370 base-long mitogenome. We conducted phylogenetic analyses using a data set including 18 publicly available asteroids rooted against five ophiuroids as outgroups. The result confirms the position of C. japonicus in the order Valvatida. The complete mitogenome of C. japonicus reported here is the first reported for the family Goniasteridae Forbes, 1841.